2017
DOI: 10.17576/jsm-2017-4610-04
|View full text |Cite
|
Sign up to set email alerts
|

Management of Collar Rot Disease in Chili by Farmyard Manure and Commercial Biofertilizers

Abstract: Collar rot of chili (Capsicum annuum L.) is a very destructive disease caused by a soil-borne fungal pathogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The isolate with the fastest ability to cause symptoms of stem rot indicates the highest level of virulence. The isolates were then identified molecularly, to determine the species (Sana et al, 2017;Shen et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The isolate with the fastest ability to cause symptoms of stem rot indicates the highest level of virulence. The isolates were then identified molecularly, to determine the species (Sana et al, 2017;Shen et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Sana, Shoaib [58] examined the collar rot disease in chili. The author showed that Sclerotium rolfsii resulted in the highest disease incidence of 73% and plant death of 60%.Sclerotium rolfsii have been proved to reduced length, fresh weight, and dry weight of root by 19%, 30%, and 40% in this experiment.…”
Section: Rotsmentioning
confidence: 99%